2021
DOI: 10.1097/j.pain.0000000000002293
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on pain for the clinic: a comprehensive review of using functional near-infrared spectroscopy to monitor its process in the brain

Abstract: Pain is a complex experience that involves sensation, emotion, and cognition. The subjectivity of the traditional pain measurement tools has expedited the interest in developing neuroimaging techniques to monitor pain objectively. Among noninvasive neuroimaging techniques, functional near-infrared spectroscopy (fNIRS) has balanced spatial and temporal resolution; yet, it is portable, quiet, and cost-effective. These features enable fNIRS to image the cortical mechanisms of pain in a clinical environment. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 179 publications
0
10
0
Order By: Relevance
“…Quantitative analysis showed that changes in the [HbO 2 ] signal acquired by fNIRS contributed 73-79% to the measured changes in total hemoglobin concentration (Hu et al, 2021). Therefore, this Comparison of activation levels in the prefrontal cortex (BA9, BA10, BA46) and motor area (BA6) with or without music intervention.…”
Section: The Fnirs Signal May Reflect Changes In Pain Conditionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Quantitative analysis showed that changes in the [HbO 2 ] signal acquired by fNIRS contributed 73-79% to the measured changes in total hemoglobin concentration (Hu et al, 2021). Therefore, this Comparison of activation levels in the prefrontal cortex (BA9, BA10, BA46) and motor area (BA6) with or without music intervention.…”
Section: The Fnirs Signal May Reflect Changes In Pain Conditionsmentioning
confidence: 86%
“…Nowadays, more scholars choose to use fNIRS for pain study, mainly because of its high temporal resolution, small size, portability, ease of wear, and insensitivity to motion artifacts. It can be used to objectively evaluate the level of brain response by measuring changes in blood flow in the cerebral cortex and thus it can be used to study the brain's response to nociception (Hu et al, 2021). It also has great potential for objective pain assessment in clinical settings and has been valued.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is a major and often used technique in the context of human brain imaging in pain research, but there are also other related techniques. One example is functional near-infrared spectroscopy (fNIRS) that allows, similarly to fMRI, to assess hemodynamic activity in the brain (Hu et al, 2021;Karunakaran et al, 2021). While fNIRS has the major advantage that it is portable and thus can be also used at the bedside, its measures are restricted to brain regions near the cortical surface.…”
Section: Brain Imagingmentioning
confidence: 99%
“…In addition, the higher resolution of fNIRS can provide more physiological information, such as heart rate variability (HRV) [21,22]. In the field of pain, an increasing number of fNIRS-based investigations have been developed [23,24]. In this study, owing to the noise level requirements of mindfulness meditation, and the use of electronic VR devices, we selected fNIRS as the neuroimaging technique to study the VRB and TMB practices by focusing on the key cortical regions for sensory processing and inhibition.…”
Section: Objectivesmentioning
confidence: 99%